Design of Virgin Coconut Oil Processing Unit on Small Scale Industry: Study on Planting Location and Delay Time of Coconut before Processing - Mulyadi, Arie Febrianto (Jurnal Teknologi Pertanian, 2011)
The objectives of this research were to gain the best delay time prior to processing for each planting locations and to design of Virgin Coconut Oil processing unit in small scale industry. This research was conducted by two steps. First, it was done by a nested randomized block design. The storage time prior to processing (1, 2, and 3 weeks) was nested on planting location (Lumajang, Malang, and Blitar region). The second step of the research was to make the design of the best treatment obtained from the first step. The result of the first step showed that the storage time was significantly different on the yield of VCO, water content, free fatty acid, peroxide value, and specific gravity. It was found that the best treatment was obtained from Blitar region with 3 weeks storage time. According to financial calculation, processing unit of Virgin Coconut Oil (VCO) in small scale industry at Blitar region was feasible. Â  Keywords: virgin coconut oil, planning of processing unit, delay time, planting location